The effect of high versus low financial leverage towards financial performance: the evidence from listed companies in Bursa Malaysia / Nur Syamih Rospi - Rospi, Nur Syamih (2018)
Financial performance is an important and vital element in measuring the stability of a company. In order to ensure that the company achieved the desired performance, it is important to determine and decide the capital structure of a company correctly. Hence, this paper is purposely discussing on how to investigate the financial performance of companies by choosing 200 companies randomly that listed in Bursa Malaysia whereas each of the company I have selected several sector or industry to measure the financial leverage each of them based on looking their financial leverage. As for the dependent variable, financial performance was indicated by return on asset meanwhile the financial leverage indicated by debt to asset ratio, debt to equity ratio and interest coverage ratio. In addition, this study period was taken from 2012 to 2017. Multiple linear regressions were used as to determine the relationship between independent variable and dependent variable.